JUSTIFICATION OF THE CHARACTERISTICS OF THE FIRE-SAFE CONDITION CONTROL SYSTEM OF THE STORAGE SYSTEM AND HYDROGEN SUPPLY - Abramov, Y.; Kryvtsova, V.; Mikhailyuk, А. (Municipal economy of cities. Series: «Economy science», 2023)
A generalized mathematical model has been introduced to describe the level of fire safety of systems for saving and supplying water, as it is presented in terms of the theory of fire safety. Such a generalized mathematical model takes into account the probability of the appearance of a combustible medium and an ignition source. It is shown that for the appearance of a combustible medium in the hydrogen storage and supply system, it is necessary and sufficient the simultaneous appearance of a combustible substance and an oxidizer. When determining the probability of an ignition source, an exponential dependence is used, the time constant of which is proportional to the value of the minimum ignition energy of the combustible medium. For the purpose of assessing the level of fire safety of systems for saving and supplying water, the control system is victorious, the functioning of which is characterized by the ability to operate without a driver. This allows you to win against the fluctuations of the health of the systems of saving and supplying water in the fire-safe and fire-safe camps, as well as to gain the counter for the fluctuations of the deaths of the first and other births. The presence of these viruses allows to induce a virus, which reflects the reliability of the functioning of such a water system. It has been wised up for some time to improve the reliability of the functioning of the system for saving and supplying water. Taking this condition into account makes it possible to formulate requirements for the control system, in particular, for the probability of its failure-free operation or for the intensity of its failures. For illustration of these minds, there were some graphical fallows, which allow to again an express assessment of the indicators of reliability and control of water supply systems. It is shown that with total control of this efficiency, which does not seem to be ideal, with an integral indicator of 0,5 and equal to the fire safety of the system for saving and supplying water 0,01, the efficiency of the controllers robotic system is more than 0,995. It should be noted that for the same minds, the control of the system is responsible for saving water supply at equal her fire safety 10-3 for an hour interval 103 , the intensity of the waters of the control system is no more to blame